EXTRACORPOREAL SHOCK-WAVE LITHOTRIPSY MONOTHERAPY OF STAGHORN CALCULI WITH DORNIER MFL 5000 - (:unkn) unknown (MARY ANN LIEBERT INC PUBL, 1993)
A retrospective study was conducted of the efficacy of extracorporeal shock wave lithotripsy (SWL) monotherapy for the management of 31 patients with staghorn calculi (mean size 5.2 cm2) . Five patients were lost to follow-up, 10 were stone-free in the end, and 11 had effective disintegration with small residual fragments. The remaining five patients required open surgery because of insufficient stone fragmentation. According to our data, SWL monotherapy is not sufficient for achieving stone-free status in patients with staghorn calculi, but it relieves obstruction and decreases the stone bulk in the majority of them.
Keywords: PERCUTANEOUS NEPHROLITHOTOMY; ANATROPHIC NEPHROLITHOTOMY; RENAL CALCULI; MANAGEMENT; STONES